Otoritas Wali Nikah dalam Perspektif Lintas Mazhab dan Kodifikasi Hukum Keluarga Islam di Indonesia - Illian hikma (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Marriage in Islamic law constitutes a sacred covenant (mīthāqan ghalīẓan) that carries theological, social, and juridical dimensions. Within this framework, the guardian (walī nikāḥ) plays a pivotal role whose legal status has long been contested across Islamic jurisprudential schools. This study examines the authority of the marriage guardian from three analytical layers: its doctrinal construction across the four major madhabs, its codification in Indonesian positive law, and its practical implementation in religious court jurisprudence. Employing a normative legal research method, this study draws on conceptual, statutory, and case approaches, with primary legal materials comprising Qur’anic verses, prophetic traditions, Law No. 1 of 1974, the Compilation of Islamic Law (KHI), and Ministerial Regulation (PMA) No. 30 of 2024. The findings reveal fundamental differences among the madhabs: the Shāfi‘ī, Mālikī, and Ḥanbalī schools treat the guardian as an essential pillar (rukun) of the marriage contract, whereas the Ḥanafī school views guardianship as a complementary element based on the concept of legal capacity (ahliyyah). Indonesian positive law, through Article 19 of the KHI, adopts the Shāfi‘ī position by designating the guardian as an obligatory rukun. The study further finds that the mechanisms of walī ‘aḍal (recalcitrant guardian) and wakalah al-walī (delegation of guardianship) serve as legal instruments that reconcile formal-procedural requirements with practical social needs, thereby affirming that guardianship norms function both as a religious requirement and as a state-administered mechanism for protecting women’s rights in marriage.